An Overview of Long Noncoding RNAs Involved in Bone Regeneration from Mesenchymal Stem Cells - Shuping Peng; Lihua Cao; Shiwei He; Yancheng Zhong; Haotian Ma; Yanru Zhang; Cijun Shuai (Hindawi Limited, 2018)
Bone regeneration is very important for the recovery of some diseases including osteoporosis and bone fracture trauma. It is a multiple-step- and multiple-gene-involved complex process, including the matrix secretion and calcium mineralization by osteoblasts differentiated from mesenchymal stem cells (MSCs) and the absorption of calcium and phosphorus by osteoclasts differentiated from hematopoietic stem cells. Long noncoding RNAs (lncRNAs) are a family of transcripts longer than 200 nt without or with very low protein-coding potential. Recent studies have demonstrated that lncRNAs are widely involved in the regulation of lineage commitment and differentiation of stem cells through multiple mechanisms. In this review, we will summarize the roles and molecular mechanism of lncRNAs including H19, MALAT1, MODR, HOTAIR, DANCR, MEG3, HoxA-AS3, and MIAT in osteogenesis ossification; lncRNA ZBED3-AS1 and CTA-941F9.9, DANCR, and HIT in chondrogenic differentiation; and lncRNA DANCR in osteoclast differentiation. These findings will facilitate the development and application of novel molecular drugs which regulate the balance of bone formation and absorption.